Pengaruh Pengetahuan Akuntansi, Pengalaman Usaha, Motivasi Kerja dan Tingkat Pendidikan Terhadap Penggunaan Infomasi Akuntansi pada Pelaku UMKM di Kota Balikpapan - Ira Pratiwi; Rihfenti Ernayani; Yanzil Azizil Yudaruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of accounting knowledge, business experience, work motivation, and education level on the use of accounting information at MSMEs in Balikpapan City. The sampling technique used purposive sampling and obtained a sample of 105 samples from 13,732 population. The data analysis technique used is validity test, reliability test and hypothesis testing using Smart-PLS 3.0 application. The result of the research shows that accounting knowledge, business experience, work motivation, and education level affect the use of accounting information in MSMEs in Balikpapan City.